ANALISIS PENGEMBANGAN INDUSTRI KREATIF BERBASIS KEARIFAN LOKAL SEBAGAI UPAYA PELESTARIAN BUDAYA MAJAPAHIT (Studi Kasus Di Kampung Majapahit, Desa Bejijong, Kecamatan Trowulan, Kabupaten Mojokerto) - Latifatun Nuzulia, Isma Farikha; Mulia, Ananda Ilham; Arifky Zuhri, Muhammad Yogi; Rahayuningtyas, Dyah (Studi Budaya Nusantara, 2018)
Abstract This research analysis development of the creative industries in the Bejijong Village, Mojokerto Regency as the one of the tourism village area. In the Bejijong Village has potential as foundry known as Brass Sheet Village, found an archaeological sites and building Majapahit House by the government. Development of creative industries is very needed for support this tourism potential. Be sides to increase economy to societies, it is also to converse Majapahit culture. This research uses qualitative research that discuss with written words. Research design uses interview and participant observant toward the society has the criteria, and also the documentation. The result of this research can give the recommendation for the government, the academician, and the society.